Non-destructive characterization method for determining high resistance formed by GaN-based material

By comparing the spectral patterns of GaN-based materials by photoluminescent devices, the high resistance of GaN-based materials was determined, and the problem of difficulty in non-destructively characterizing the high resistance of GaN-based materials in the prior art was solved, and a fast and intuitive high resistance judgment was achieved.

CN119560397APending Publication Date: 2025-03-04NANCHANG UNIV +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411653929.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to directly and non-destructively characterize whether doped carbon elements in GaN-based materials form high resistance, and conventional methods require destructive testing and have a long process flow.

Method used

The reference and target spectrograms of the GaN-based material were obtained by a photoluminescent device, and the intensity of the GaN intrinsic luminescence peak and the yellow band luminescence peak were compared to determine whether the target GaN-based material formed a high resistance.

Benefits of technology

It realizes rapid and non-destructive characterization of high resistance of GaN-based materials, simplifies the process flow, accelerates R&D feedback, and intuitively determines the results without complex data processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560397A_ABST
    Figure CN119560397A_ABST
Patent Text Reader

Abstract

The invention discloses a non-destructive characterization method for determining high resistance formed by doping a GaN-based material with a carbon element, and relates to the technical field of semiconductor devices, and the method comprises the steps: obtaining a spectrogram of a reference GaN-based epitaxial wafer and a spectrogram of a target GaN-based epitaxial wafer through a photoluminescence device; according to the spectrogram, determining a first reference PL intensity, a second reference PL intensity, a first target PL intensity and a second target PL intensity respectively corresponding to a GaN intrinsic luminescence peak and a yellow band luminescence peak in the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer; and if the first target PL intensity is less than or equal to 10% of the first reference PL intensity and the second target PL intensity is less than or equal to 10% of the second reference PL intensity, determining that the target GaN-based epitaxial wafer forms high resistance. The characterization method is simple, convenient and rapid, reduces chip manufacturing procedures, accelerates the feedback speed of production and research and development, reduces trial and error and manufacturing cost, is visual in judgment result, does not need complex data processing, and belongs to non-destructive testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor devices, and in particular to a non-destructive characterization method for determining whether a GaN-based material forms high resistance. Background Art

[0002] GaN-based materials are third-generation semiconductors with large bandgap widths. They can form alloys to modulate the energy bands and achieve adjustable emission wavelengths from infrared to ultraviolet. Therefore, GaN-based materials are suitable for the preparation of light-emitting diodes, ultraviolet light-emitting diodes, detectors and other equipment, and have broad application prospects in the fields of solid-state semiconductor lighting and display, medical lighting and military detection. At the same time, GaN-based materials have the advantages of large bandgap widths, high breakdown field strengths, and high saturated electron drift velocities. They can produce high-density two-dimensional electron gas through polarization effects. Therefore, GaN electronic devices can be used in the fields of efficient power conversion, high-frequency signal modulation, high-voltage controllable switches, and high-speed information processing, and have great application potential in the fields of power and radio frequency electronic devices.

[0003] Technologies such as metal organic chemical vapor deposition (MOCVD) are often used to achieve heteroepitaxial growth and in-situ doping of GaN-based materials. Due to the presence of carbon groups in the MO organic source, carbon contamination is inevitable in the MOCVD growth system. At the same time, in GaN power devices and RF devices, it is necessary to obtain high-resistance GaN by doping with a higher concentration of carbon elements to reduce the off-state leakage of the device and increase the breakdown voltage. The resistivity of n-type GaN is usually between a few milliohm-cm and tens of milliohm-cm, while the resistivity of high-resistance GaN required for power devices and RF devices needs to be greater than hundreds of ohm-cm. However, during the growth process of GaN materials, there are few means to characterize whether the doped carbon elements form high-resistance GaN. Conventional characterization methods are destructive and have a long manufacturing process. The grown epitaxial wafer needs to go through the chip manufacturing process, evaporate the metal electrode, and then perform the Hall test to obtain the resistivity for judgment; for example, Chinese patent CN 103578986 A provides a method for preparing a high-resistance GaN film. This patent determines whether the sample forms a high resistance by measuring the resistivity of the sample. If the epitaxial wafer can be directly characterized and judged non-destructively, the R&D feedback process can be accelerated and the process flow can be greatly reduced. Summary of the invention

[0004] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a non-destructive characterization method for determining whether a GaN-based material forms a high resistance, which can quickly characterize whether the carbon element doped in the GaN-based material forms a high resistance. The innovation of the present invention lies in providing a new non-destructive characterization method that can directly test and characterize the epitaxial wafer to determine whether the carbon element doped in the GaN-based material forms a high resistance.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a non-destructive characterization method for determining whether a GaN-based material forms a high resistance, comprising the following steps:

[0007] By means of a photoluminescence device, a reference spectrum graph and a target spectrum graph corresponding to a reference GaN-based epitaxial wafer and a target GaN-based epitaxial wafer are obtained respectively; wherein the reference GaN-based epitaxial wafer is a GaN-based epitaxial wafer that has not been carbon-doped, and the target GaN-based epitaxial wafer is a GaN-based epitaxial wafer that has been carbon-doped at a preset concentration;

[0008] According to the reference spectrum, determining a first reference PL intensity and a second reference PL intensity corresponding to a GaN intrinsic luminescence peak and a yellow band luminescence peak in the reference GaN-based epitaxial wafer, respectively;

[0009] According to the target spectrum, determining a first target PL intensity and a second target PL intensity corresponding to a GaN intrinsic luminescence peak and a yellow band luminescence peak in the target GaN-based epitaxial wafer, respectively;

[0010] Based on the fact that the first target PL intensity is ≤10% of the first reference PL intensity and the second target PL intensity is ≤10% of the second reference PL intensity, it is determined that the target GaN-based epitaxial wafer forms a high resistance.

[0011] In GaN-based materials, in addition to the intrinsic luminescence peak, there is also a yellow band luminescence peak. The source of the yellow band luminescence peak is often considered to be caused by the luminescence formed by the deep energy level of Ga vacancy defects or carbon atoms replacing N atoms. Since Ga vacancies and C atoms are inevitably present in the MOCVD growth process of GaN, the yellow band luminescence peak is often considered to be caused by the luminescence formed by the deep energy level of Ga vacancy defects or carbon atoms replacing N atoms. N Therefore, there are GaN intrinsic luminescence peaks and yellow band luminescence peaks in undoped carbon samples or GaN-based materials with low carbon doping concentrations. When the concentration of doped carbon increases, the deep energy level tends to saturate, and carbon atoms tend to replace Ga atoms to form shallow donor energy levels, which form self-compensation with deep energy level acceptors to achieve high-resistance GaN. Ga After the shallow donor energy level is formed, the intrinsic luminescence peak of GaN will weaken; and after the shallow donor energy level compensates the deep energy level acceptor, the yellow band luminescence peak will weaken. Therefore, the strength of the GaN intrinsic luminescence peak and the yellow band luminescence peak can be used to determine whether high resistance is formed in the GaN-based material. When the PL intensity of the GaN intrinsic luminescence peak and the yellow band luminescence peak at any carbon doping concentration is ≤10% of the PL intensity of GaN without carbon doping at the same time, it indicates that the GaN-based material with this carbon doping concentration has achieved high resistance; when the PL intensity of the GaN intrinsic luminescence peak and the yellow band luminescence peak at any carbon doping concentration is not ≤10% of the PL intensity of GaN without carbon doping at the same time, it indicates that the GaN-based material with this carbon doping concentration has not achieved high resistance.

[0012] Optionally, the method specifically comprises the following steps:

[0013] Obtaining, by means of a photoluminescence device, under the same test conditions, spectra of GaN intrinsic luminescence peaks corresponding to the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer, which correspond to the first reference PL intensity and the first target PL intensity, respectively;

[0014] Obtaining, by means of a photoluminescence device, under the same test conditions, spectrum graphs of yellow-band luminescence peaks corresponding to the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer, which correspond to the second reference PL intensity and the second target PL intensity, respectively;

[0015] comparing the first reference PL intensity with the first target PL intensity, and comparing the second reference PL intensity with the second target PL intensity;

[0016] If the first target PL intensity is ≤10% of the first reference PL intensity, and the second target PL intensity is ≤10% of the second reference PL intensity, it is determined that the target GaN-based epitaxial wafer forms a high resistance.

[0017] Optionally, the laser wavelength of the photoluminescent device is one or a combination of several lasers with a wavelength of ≤550 nm, and the receiving wavelength of the receiving spectrometer is one or a combination of several spectrometers with a wavelength of ≥300 nm.

[0018] Optionally, the test power of the photoluminescent device is ≥1 mW, and the test time is ≥1 ms.

[0019] Optionally, the PL laser wavelength for testing the intrinsic luminescence peak of GaN is 213 nm, and the receiving wavelength of the receiving spectrometer is 210 nm-430 nm.

[0020] Optionally, the test conditions of the GaN intrinsic luminescence peak include: laser power of 2.5 mW, test time of 50 ms, test starting wavelength range of 260 nm-430 nm, and test resolution of 1.44 mm.

[0021] Optionally, the PL laser wavelength for testing the yellow band luminescence peak is 375 nm, and the receiving wavelength of the receiving spectrometer is 380 nm-830 nm.

[0022] Optionally, the test conditions of the yellow band luminescence peak include: laser power of 2.5 mW, test time of 50 ms, test starting wavelength range of 400 nm-750 nm, and test resolution of 1.44 mm.

[0023] Optionally, the PL peak wavelength of the GaN intrinsic light emitting peak is 358-368nm.

[0024] Optionally, the PL peak wavelength of the yellow band luminescence peak is 558-578nm.

[0025] The present invention has at least one of the following beneficial effects:

[0026] The present invention can quickly determine whether the carbon doped in the GaN-based material forms a high resistance by directly characterizing the epitaxial wafer. Compared with the characterization method of determining the resistivity after the epitaxial wafer is manufactured into a chip, the present invention speeds up the R&D feedback process and greatly reduces the process flow. At the same time, the determination results of the characterization method of the present invention are more intuitive and do not require complex data processing. In addition, the characterization method of the present invention is a non-destructive test. After the test, the epitaxial wafer can be tested and produced for other requirements without affecting the R&D and production processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 PL spectra of GaN intrinsic luminescence peaks of samples with different carbon doping concentrations in the present invention: (a) without carbon doping, (b) with carbon doping concentration of 1×10 18 atom / cm 3 , (c) carbon doping concentration 2×10 18 atom / cm 3 , (d) carbon doping concentration 4×10 18 atom / cm 3 , (e) carbon doping concentration 1×10 19 atom / cm 3 , (f) carbon doping concentration 2×10 19 atom / cm 3 .

[0028] Figure 2 PL spectra of the yellow band luminescence peak of samples with different carbon doping concentrations of the present invention: (a) without carbon doping, (b) with carbon doping concentration of 1×10 18 atom / cm 3 , (c) carbon doping concentration 2×10 18 atom / cm 3 , (d) carbon doping concentration 4×10 18 atom / cm 3 , (e) carbon doping concentration 1×10 19 atom / cm 3 , (f) carbon doping concentration 2×10 19 atom / cm 3 . DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] An embodiment of the present invention provides a non-destructive characterization method for determining whether a GaN-based material forms a high resistance, comprising the following steps:

[0031] Obtaining, by means of a photoluminescence device, under the same test conditions, spectra of GaN intrinsic luminescence peaks corresponding to the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer, which correspond to the first reference PL intensity and the first target PL intensity, respectively;

[0032] Obtaining, by means of a photoluminescence device, under the same test conditions, spectrum graphs of yellow-band luminescence peaks corresponding to the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer, which correspond to the second reference PL intensity and the second target PL intensity, respectively;

[0033] comparing the first reference PL intensity with the first target PL intensity, and comparing the second reference PL intensity with the second target PL intensity;

[0034] If the first target PL intensity is ≤10% of the first reference PL intensity, and the second target PL intensity is ≤10% of the second reference PL intensity, it is determined that the target GaN-based epitaxial wafer forms a high resistance.

[0035] In some specific embodiments, the characterization method specifically comprises the following steps:

[0036] Step 1: growing a GaN-based epitaxial wafer not doped with carbon on a substrate to obtain a reference GaN-based epitaxial wafer; growing a GaN-based epitaxial wafer with a preset carbon concentration on a substrate to obtain a target GaN-based epitaxial wafer;

[0037] Step 2: directly test the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer obtained in step 1 using a photoluminescence device (PL), and obtain the PL spectra of the GaN intrinsic luminescence peak of the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer respectively under the same test conditions, and obtain the PL spectra of the yellow band luminescence peak of the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer respectively under the same test conditions, wherein the PL peak wavelength of the GaN intrinsic luminescence peak is about 365nm, and the PL peak wavelength of the yellow band luminescence peak is about 560nm.

[0038] Step 3: Compare the PL spectra of the GaN intrinsic luminescence peak of the reference GaN-based epitaxial wafer obtained in step 2 with the target GaN-based epitaxial wafer, and compare the PL spectra of the yellow band luminescence peak of the reference GaN-based epitaxial wafer obtained in step 2 with the target GaN-based epitaxial wafer.

[0039] When the PL intensity of the GaN intrinsic luminescence peak of the target GaN-based epitaxial wafer is ≤10% of the PL intensity of the intrinsic luminescence peak of the reference GaN-based epitaxial wafer, and at the same time, the PL intensity of the yellow band luminescence peak of the target GaN-based epitaxial wafer is ≤10% of the PL intensity of the yellow band luminescence peak of the reference GaN-based epitaxial wafer, it is determined that the target GaN-based material has achieved high resistance.

[0040] The characterization object of the present invention is a GaN-based material with any carbon doping concentration, and the characterization method is to test the GaN intrinsic luminescence peak and the yellow band luminescence peak of the GaN-based material with any doping concentration. When the GaN intrinsic luminescence peak and the yellow band luminescence peak are both ≤10% of the PL intensity of undoped GaN, it can be determined that the GaN-based material with this carbon doping concentration has formed a high resistance. The present invention can quickly determine whether the carbon doping in the GaN-based material has formed a high resistance by directly characterizing the epitaxial wafer. Compared with the characterization method of determining the resistivity after the epitaxial wafer is manufactured into a chip, the present invention speeds up the R&D feedback process and greatly reduces the process flow. At the same time, the determination result of the characterization method of the present invention is more intuitive and does not require complex data processing. In addition, the characterization method of the present invention belongs to non-destructive testing. After the test, the epitaxial wafer can be tested and produced for other requirements without affecting the R&D and production processes.

[0041] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0042] Implementation 1:

[0043] In this embodiment, the non-destructive characterization method for determining whether the GaN-based material doped with carbon elements forms a high resistance specifically includes the following steps:

[0044] Step 1: Use MOCVD to grow undoped carbon and doped carbon with a concentration of 1×10 18 atom / cm 3 , 2×10 18 atom / cm 3 , 4×10 18 atom / cm 3 , 1×10 19 atom / cm 3 and 2×10 19 atom / cm 3 GaN-based epitaxial wafers, a total of 6 groups of samples.

[0045] Step 2: Use the PL photoluminescence equipment to directly test the six groups of samples with different carbon concentrations prepared in step 1. The PL laser wavelength for testing the intrinsic emission peak of GaN is 213nm, and the receiving wavelength of the spectrometer is 210nm-430nm. Test conditions: laser power is 2.5mW, test time is 50ms, test starting wavelength range is 260nm-430nm, and test resolution is 1.44mm.

[0046] Step 3: Compare the GaN intrinsic luminescence peak PL spectra of the samples of various carbon doping concentrations obtained in step 2, such as Figure 1 As shown in the figure, it can be clearly seen that the PL peak of GaN intrinsic luminescence is about 365nm. When no carbon is doped, the PL intensity of the GaN intrinsic luminescence peak is 2163a.u.; when the carbon doping concentration is 1×10 18 atom / cm 3 When the concentration of carbon doping is 2×10 18 atom / cm 3 When the concentration of carbon doping is 4×10 18 atom / cm 3 , 1×10 19 atom / cm 3 and 2×10 19 atom / cm 3 When the PL intensity of GaN intrinsic luminescence peak is less than 10a.u.

[0047] Step 4: Use the PL photoluminescence device to directly test the six groups of samples with different carbon element concentrations prepared in step 1. The PL laser wavelength of the yellow band luminescence peak is 375nm, and the receiving wavelength of the spectrometer is 380nm-830nm. Test conditions: laser power is 2.5mW, test time is 50ms, test starting wavelength range is 400nm-750nm, and test resolution is 1.44mm.

[0048] Step 5: Compare the yellow band luminescence peak PL spectra of the samples of each carbon doping concentration obtained in step 4, such as Figure 2 As shown in the figure, it can be clearly seen that the yellow band luminescence PL peak in GaN-based materials is about 560nm, and the half-peak width of the spectrum is very large. The PL intensity of the undoped yellow band luminescence peak is 628a.u.; when the concentration of doped carbon is 1×10 18 atom / cm 3 When the concentration of carbon doping is 2×10 18 atom / cm 3When the concentration of carbon doping is 4×10 18 atom / cm 3 When the concentration of carbon doping is 1×10 19 atom / cm 3 and 2×10 19 atom / cm 3 When the yellow band luminescence peak intensity is less than 20 a.u.

[0049] Step 6: Combine the results of step 3 and step 5 to make a judgment. When the carbon doping concentration is 4×10 18 atom / cm 3 When the carbon doping concentration is 4×10 18 atom / cm 3 When the carbon doping concentration is ≥4×10 18 atom / cm 3 When GaN is used, it achieves high resistance.

[0050] In order to verify the accuracy of the method in Example 1, the six groups of samples in step one are also cut into 1cm×1cm samples after evaporating metal electrodes according to the requirements of the Hall test. Four electrodes are prepared at the four corners of the sample, and the electrode size is 1000um. It is planned to conduct a Hall test to obtain the resistivity. However, during the test, it was found that the electrodes of the six groups of samples did not form ohmic contact, and the Hall test could not be performed. The main reason is that the resistivity of the six groups of samples is relatively high, and it is difficult for the electrodes to form ohmic contact. Therefore, another test method was used to test the vertical withstand voltage of the six groups of samples at 1uA. Under the same GaN thickness, the higher the resistance, the greater the vertical withstand voltage. As a result, the vertical withstand voltages of the six groups of samples were 349V, 360V, 369V, 530V, 550V, and 560V, respectively. When the carbon doping concentration is ≤2×10 18 atom / cm 3 When the carbon doping concentration doubles, the vertical withstand voltage only increases by about 10V; when the carbon doping concentration is ≥4×10 18 atom / cm 3 The vertical withstand voltage increases significantly when the carbon doping concentration is ≥4×10 18 atom / cm 3 The GaN-based material achieves high resistance, which is consistent with the test results of Example 1, indicating that the method of Example 1 can accurately determine whether the GaN-based material has formed a high resistance.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A non-destructive characterization method for determining whether a GaN-based material forms a high resistance, characterized in that: The following steps are involved: By means of a photoluminescence device, a reference spectrum graph and a target spectrum graph corresponding to a reference GaN-based epitaxial wafer and a target GaN-based epitaxial wafer are obtained respectively; wherein the reference GaN-based epitaxial wafer is a GaN-based epitaxial wafer that has not been carbon-doped, and the target GaN-based epitaxial wafer is a GaN-based epitaxial wafer that has been carbon-doped at a preset concentration; According to the reference spectrum, determining a first reference PL intensity and a second reference PL intensity corresponding to a GaN intrinsic luminescence peak and a yellow band luminescence peak in the reference GaN-based epitaxial wafer, respectively; According to the target spectrum, determining a first target PL intensity and a second target PL intensity corresponding to a GaN intrinsic luminescence peak and a yellow band luminescence peak in the target GaN-based epitaxial wafer, respectively; Based on the fact that the first target PL intensity is ≤10% of the first reference PL intensity and the second target PL intensity is ≤10% of the second reference PL intensity, it is determined that the target GaN-based epitaxial wafer forms a high resistance.

2. The characterization method according to claim 1, characterized in that The method specifically comprises the following steps: Obtaining, by means of a photoluminescence device, under the same test conditions, spectra of GaN intrinsic luminescence peaks corresponding to the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer, which correspond to the first reference PL intensity and the first target PL intensity, respectively; Obtaining, by means of a photoluminescence device, under the same test conditions, spectrum graphs of yellow-band luminescence peaks corresponding to the reference GaN-based epitaxial wafer and the target GaN-based epitaxial wafer, which correspond to the second reference PL intensity and the second target PL intensity, respectively; comparing the first reference PL intensity with the first target PL intensity, and comparing the second reference PL intensity with the second target PL intensity; If the first target PL intensity is ≤10% of the first reference PL intensity, and the second target PL intensity is ≤10% of the second reference PL intensity, it is determined that the target GaN-based epitaxial wafer forms a high resistance.

3. The characterization method according to claim 1 or 2, characterized in that: The laser wavelength of the photoluminescent device is one or a combination of several lasers with a wavelength of ≤550nm, and the receiving wavelength of the receiving spectrometer is one or a combination of several spectrometers with a wavelength of ≥300nm.

4. The characterization method according to claim 1 or 2, characterized in that: The test power of the photoluminescent device is ≥1 mW, and the test time is ≥1 ms.

5. The characterization method according to claim 1 or 2, characterized in that: The PL laser wavelength for testing the intrinsic luminescence peak of GaN is 213 nm, and the receiving wavelength of the receiving spectrometer is 210 nm-430 nm.

6. The characterization method according to claim 5, characterized in that The test conditions of the GaN intrinsic luminescence peak include: laser power of 2.5 mW, test time of 50 ms, test starting wavelength range of 260 nm-430 nm, and test resolution of 1.44 mm.

7. The characterization method according to claim 1 or 2, characterized in that: The PL laser wavelength for testing the yellow band luminescence peak is 375 nm, and the receiving wavelength of the receiving spectrometer is 380 nm-830 nm.

8. The characterization method according to claim 7, characterized in that: The test conditions of the yellow band luminescence peak include: laser power of 2.5 mW, test time of 50 ms, test starting wavelength range of 400 nm-750 nm, and test resolution of 1.44 mm.

9. The characterization method according to claim 1 or 2, characterized in that: The PL peak wavelength of the GaN intrinsic luminescence peak is 358nm-368nm.

10. The characterization method according to claim 1 or 2, characterized in that: The PL peak wavelength of the yellow band luminescence peak is 558nm-578nm.

Citation Information

Patent Citations

  • Method for manufacturing high-resistance GaN thin film

    CN103578986A